6 The first 6 months: what did one hospital supportive and palliative care team (SPCT) experience during the first 6 months of the COVID-19 pandemic?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Malik, Farida; Winter, Jayne; Matthews, David
Abstract : Background: 26% of UK CoVID-19 patients requiring hospitalization die, often with high symptom burden. Needs of non-COVID patients, however, must also be met. Studies have focused on hospital PC COVID activity but understanding the whole experience of work in the first 6 months of the pandemic is paramount to help future service planning. Methods: 1.Retrospective case series review of all patients referred to SPCT (COVID and non-Covid) 1st Mar 20–31st Aug 20 and associated service level activity. Variables collected: Baseline demographic/clinical characteristics, outcomes, Phase of Illness (POI), AKPS. Results compared with same 6-month period in 2019. 2.Semi-structured anonymised online survey of all SPCT members regarding working experiences and needs. Results: Total of 904 patient episodes: 48 COVID, 856 Non-COVID (compared with total of 826 patient episodes in 2019). Regarding 48 COVID cases, mean age 81 years, mean initial AKPS 26%. 60% in Dying phase, mean caseload time 4.1 days with 80% dying in hospital. SPCT involved in 30% of all COVID deaths in hospital. For Non-COVID episodes, mean age 78 years and AKPS 32%; 27% in Dying phase, 35% unstable, 31% deteriorating. 43% died in hospital with 24% discharged home. For 2019 data, mean AKPS 32% with 32% Dying phase, 35% unstable and 21% deteriorating. One-third (9/12) SPC team had suspected COVID symptoms, a quarter self-isolated. Service developments included rapid introduction of 7-day CNS service & EOL COVID guideline introduction. COVID experiences centred on rapid patient deterioration, patient communication difficulties and challenging remote communication with families. Impact on own personal wellbeing also cited. For Non-COVID, similar experiences of activity compared with pre-COVID but possible later presentations highlighted and more symptomatic. Conclusion: In addition to managing COVID patients, the SPCT also saw more non-COVID patients compared with 2019. Planning for future phases underway to continue the service developments highlighted and maintain team wellbeing.